FRAMING ANALYSIS OF PRESIDENTIAL ASSISTANCE FOR EARTHQUAKE VICTIMS IN LOMBOK (PIKIRAN RAKYAT - KOMPAS) - Mutiara Ramadhan; Teti Sobari (IKIP Siliwangi, 2018)
Not a few news will be delivered differently from several print media. This is the strategy of the writer to bring the opinion of the reader to the news. Not a few mass media that support one of the figures, so that the media raises the image of the figure. To analyze the news, framing analysis can be done. The purpose of this study was to find out how the Pikiran Rakyat and Kompas in compiling a story were seen from a syntactic, script, thematic, and rhetorical structure. The method used is qualitative research. The text that is the object of research is the text about the President's assistance to earthquake victims in Lombok which is contained in the media of Pikiran Rakyat and Kompas. Based on the results of the study, it was revealed that the Pikiran Rakyat Newspaper explained more details of the activities carried out by the President, so that the figure of this nation's leader was very concerned. Whereas in the Kompas newspaper the contents of the news only summarized the President's activities while in Lombok.